44.1k views
5 votes
Having trouble.. help?

Having trouble.. help?-example-1

2 Answers

2 votes
A. {(x, y): y= x + 3}
User DougN
by
5.4k points
6 votes

Answer:

(A)
y = x+3

Explanation:

Using the values of (-6, -3), (3,6), and (5,8) we can substitute the values into each equation and see if the equation meets the requirements for all 3.

Let's test A first.


-3 = -6+3

Correct, let's try the second pair.


6 = 3+3

Correct, let's try the third pair.


8 = 5+3

So yes, this equation works.

For fun, let's try the other equations.

Let's test B.


-3 = -6-3

This is not true as -6 -3 = -9. So this equation is immediately ruled out.

Let's test C.


-3 = 2\cdot-6

Again this doesn't work, as -6 times 2 is -12. So this equation is also ruled out.

Let's try D.


-3 = (1)/(2)\cdot-6

This works, as half of -6 is -3 - however the equation will only work if all 3 pairs work for it.

Let's try the second pair.


6 = (1)/(2)\cdot3

This doesn't work, as half of 3 is 1.5. This equation is also ruled out.

Therefore, A is the only equation that works with these pairs.

Hope this helped!

User Nimit Joshi
by
6.3k points